2004
DOI: 10.1130/g19919.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sediment supply and avulsion frequency in braided rivers

Abstract: The interplay between sediment supply (S s ), sedimentation rate (S r ), and the frequency of channel avulsion (A f ) exerts a primary control on alluvial architecture. In order to investigate the effect of sediment supply on avulsion frequency, four Froude-scale model experiments of an aggrading braided river were undertaken in which the magnitude of S s was progressively increased over an eightfold range. The value of A f increases at a rate slower than the increase in S s , contrary to the trend previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 12 publications
9
96
2
Order By: Relevance
“…Sediment flux increased, the avulsion rate first increased and then stabilized as mass flows began to influence deposition, and the experiments also showed that less total sediment volume was needed to trigger an avulsion as the sediment supply rate increased. This is in contrast to the findings of Ashworth et al (2004Ashworth et al ( , 2006 who used Froude-scale modelling to observe avulsions in braided rivers and found that avulsion frequency increased with sediment supply but at a rate slower than the increase in the sediment feed rate. Ashworth et al (2004) concluded that the most probable cause of this difference was the dependency of sediment supply and avulsion frequency on bed slope; the steeper fan slopes of Bryant et al (1995) created multi-channel systems that are inherently less stable.…”
Section: Figurecontrasting
confidence: 55%
See 1 more Smart Citation
“…Sediment flux increased, the avulsion rate first increased and then stabilized as mass flows began to influence deposition, and the experiments also showed that less total sediment volume was needed to trigger an avulsion as the sediment supply rate increased. This is in contrast to the findings of Ashworth et al (2004Ashworth et al ( , 2006 who used Froude-scale modelling to observe avulsions in braided rivers and found that avulsion frequency increased with sediment supply but at a rate slower than the increase in the sediment feed rate. Ashworth et al (2004) concluded that the most probable cause of this difference was the dependency of sediment supply and avulsion frequency on bed slope; the steeper fan slopes of Bryant et al (1995) created multi-channel systems that are inherently less stable.…”
Section: Figurecontrasting
confidence: 55%
“…This is in contrast to the findings of Ashworth et al (2004Ashworth et al ( , 2006 who used Froude-scale modelling to observe avulsions in braided rivers and found that avulsion frequency increased with sediment supply but at a rate slower than the increase in the sediment feed rate. Ashworth et al (2004) concluded that the most probable cause of this difference was the dependency of sediment supply and avulsion frequency on bed slope; the steeper fan slopes of Bryant et al (1995) created multi-channel systems that are inherently less stable. The probability of avulsion is therefore likely to be greater with a smaller change in sediment supply, leading to the conclusion that alluvial fans are more prone to avulsion events than river systems.…”
Section: Figurecontrasting
confidence: 55%
“…Previous observations support this intuition, but there is no consensus yet about the slope's physical origin, which involves the response of a single channel to sediment transport and its destabilization into multiple threads (Whipple et al, 1998;Ashworth et al, 2004). We do not find any correlation between sediment discharge and slope in our experiment (Fig.…”
Section: Mass Balancesupporting
confidence: 63%
“…Producing experimental alluvial fans has become common in geomorphology (Schumm et al, 1987;Bryant et al, 1995;Whipple et al, 1998;Ashworth et al, 2004;Van Dijk et al, 2009;Clarke et al, 2010;Powell et al, 2012;Reitz and Jerolmack, 2012;Clarke, 2015). Here, we use a setup similar to that of, for example, Whipple et al (1998) to generate a radially symmetric fan over a horizontal basal surface (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation